Putting one health to the test: Operational challenges and critical reflections from the global South - Mridula Mary Paul; Sunita Pradhan; Aarti Chettri; Sarala Khaling; Abi T. Vanak (One Health)
One Health as a policy framework to tackle zoonoses has gained wide-ranging validation with multiple international organizations throwing their collective might behind it. Such endorsement has convinced several governments to adopt One Health as a national strategy to address zoonoses. Although some argue that One Health is so many things that there are in fact multiple ‘One Healths’, others find that most international policy documents that use the One Health framing contain certain key recommendations, with intersectoral coordination and disease surveillance prominent among them. In this paper we examine whether and how One Health travels in a sub-national setting in a developing country context such as that of India, with particular focus on intersectoral coordination. We draw on documentary analysis, semi-structured interviews, and workshops with government officials across key sectoral agencies at the district level, to understand prevalent institutional mechanisms in place to address zoonoses in such a setting. We locate our study in the district of Gyalshing in the state of Sikkim in India, which is a potential zoonoses ‘hotspot’ given its location within the biodiverse Indian Himalayan Region, with numerous avenues for human-animal interactions, and burgeoning human population linked to its tourism-run economy. We outline successful cases where certain zoonotic diseases could be tackled, while also highlighting structural constraints that need to be borne in mind while planning or advocating One Health as a blanket policy prescription. In doing so, we draw attention to the political dimensions of global health policies, and question whether One Health can be uncritically deployed in developing country contexts.